Health professionals' knowledge, attitude and practices towards pharmacovigilance in Nepal - Palaian S; Ibrahim MI; Mishra P (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Pharmacovigilance can be helpful in protecting consumers from harmful effects of medicines. Healthcare professionals should consider Adverse Drug Reaction (ADR) reporting as their professional obligation and should be aware of the existing pharmacovigilance mechanisms in their countries. In Nepal, pharmacovigilance activities were initiated in 2004. Objectives: The present study evaluated the knowledge, attitude and practices (KAP) of the healthcare professionals towards ADRs and pharmacovigilance in Manipal Teaching Hospital (MTH), a tertiary care teaching hospital attached to the regional pharmacovigilance center in western Nepal. Methods: A cross-sectional study was carried out in 2007 using a pretested (Cronbach alpha=0.72) questionnaire having 25 questions (15 questions on knowledge, 5 on attitude and 5 on practice). The correct/positive responses were given a score of '2' and the wrong/negative responses '1', maximum possible score of '50'. Results: A total of 131 responses were obtained among which 42 were incomplete and remaining 89 [females 49 (55.1%)] were analyzed. Of the 89 professionals, 29 (32.6%) were doctors, 46 (51.8) nurses and 14 (15.7%) pharmacists. The mean age was 28.32 (SD=8.46) years and the median (interquartile range) of duration of the service 14.5 (6-36) months. The total KAP scores was 40.06 (SD=3.51) for doctors, 38.92 (SD=4.83) for pharmacists, and 35.82 (SD=3.75) for nurses. Among the 89 professionals, 59 (62.3%) had not reported even a single ADR to the pharmacovigilance center. Conclusion: The healthcare professionals at the MTH had a poor KAP towards ADRs and pharmacovigilance and there is a need for educational and awareness intervention for these professionals.